AN IMPLICATION OF ACTINOMYCETES ON HUMAN WELL-BEING: A REVIEW - BAWAZIR, ALI MOHAMMED ABDULLAH; PALAKSHA; SHANTARAM, MANJULA (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
This review conceptualizes about the actinomycetes and its contribution to human health by playing a key role as bioactive secondary metabolites, such as enzymes, antibiotics and pigments, leading to their diverse applications and use in various industries. These searches have been uncommonly successful, and around 66% of naturally happening antibiotics, including many medically important, have been isolated from actinomycetes. The speedy occurrence of antimicrobial resistance among pathogens has led to a renewed interest to search for novel antimicrobial agents, but these antibiotics are not enough for the treatment of all diseases because there is a berserk requirement for a novel actinomycetes to combat against the antibiotic-resistant strains of pathogenic microorganisms, which are quickly expanding bit by bit. Actinomycetes are the important providers to the pharmaceutical and other industries and are well known for their capacity to produce secondary metabolites many of which are active against pathogenic microorganisms.